KONTRIBUSI HARGA DAN PENINGKATAN KUALITAS PELAYANAN PADA KEPUTUSAN PEMBELIAN KONSUMEN UNTUK BERBELANJA PADA ALFAMART CABANG CIBEUREUM KOTA SUKABUMI: Manajemen sumberdaya manusia - Asep Suryana, SE., M.AK (P3M STIE PASIM Sukabumi, 2017)
This research was conducted at Alfamart Cibeureum Branch, Sukabumi City. The purpose of this study is to determine the effect of price and product quality improvement simultaneously on consumer purchasing decisions to shop at Alfamart Cibeureum Branch, Sukabumi City. The research method used is the Associative Descriptive method. The population in this study were consumers who shopped at Alfamart Cibereum City Branch for one month and the sample used was 94 people obtained by using non-probability sampling with judgment sampling technique. Meanwhile, to test the research instrument using validity, reliability, and hypothesis testing. used t test and ui f, then analysis of the relationship used Pearson correlation, coefficient of determination and multiple linear regression analysis. Based on the results of the analysis that has been carried out, it can be seen that the correlation test shows that the correlation value of Price on Purchase Decisions is 0.947 and includes a very strong correlation category because it is in the interval